A liquid chromatography-mass spectrometric method for the detection of cyclic β-amino fatty acid lipopeptides - Urajová, Petra; Hájek, Jan; Wahlsten, Matti; Jokela, Jouni; Galica, Tomáš; Fewer, David P; Kust, Andreja; Zapomělová-Kozlíková, Eliška; Delawská, Kateřina; Sivonen, Kaarina; Kopecký, Jiří; Hrouzek, Pavel (Journal of chromatography. A, 2016)
Bacterial lipopeptides, which contain β-amino fatty acids, are an abundant group of bacterial secondary metabolites exhibiting antifungal and/or cytotoxic properties. Here we have developed an LC-HRMS/MS method for the selective detection of β-amino fatty acid containing cyclic lipopeptides. The method was optimized using the lipopeptides iturin A and puwainaphycin F, which contain fatty acids of similar length but differ in the amino acid composition of the peptide cycle. Fragmentation energies of 10-55eV were used to obtain the amino acid composition of the peptide macrocycle. However, fragmentation energies of 90-130eV were used to obtain an intense fragment specific for the β-amino fatty acid (CnH2n+2N(+)). The method allowed the number of carbons and consequently the length of the β-amino fatty acid to be estimated. We identified 21 puwainaphycin variants differing in fatty acid chain in the crude extract of cyanobacterium Cylindrospermum alatosporum using this method. Analogously 11 iturin A variants were detected. The retention time of the lipopeptide variants showed a near perfect linear dependence (R(2)=0.9995) on the length of the fatty acid chain in linear separation gradient which simplified the detection of minor variants. We used the method to screen 240 cyanobacterial strains and identified lipopeptides from 8 strains. The HPLC-HRMS/MS method developed here provides a rapid and easy way to detecting novel variants of cyclic lipopeptides.
Keywords: Cyanobacteria; Lipopeptides; mastné kyseliny; Antifungal Agents; sinice; Fatty Acids; chemické techniky analytické; Chromatography, Liquid; Fatty acid; hmotnostní spektrometrie; lipopeptidy; Bacteria; Mass Spectrometry; Peptide; Amino Acids; aminokyseliny; antifungální látky; LC-HRMS; chromatografie kapalinová; Chemistry Techniques, Analytical